2010
DOI: 10.1021/ja9085148
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Characterization of N-Oxide Tripod Amphiphiles

Abstract: Tripod amphiphiles are designed to promote the solubilization and stabilization of intrinsic membrane proteins in aqueous solution; facilitation of crystallization is a long-range goal. Membrane proteins are subjects of extensive interest because of their critical biological roles, but proteins of this type can be difficult to study because of their low solubility in water. The nonionic detergents that are typically used to achieve solubility can have the unintended effect of causing protein denaturation. Trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…At this time, it is not clear whether or not ganglio-TPAs form small PDCs relative to those formed with DDM. However, our previous study may shed light on the topic [37]. We recently reported the crystal structures of several N -oxide TPAs and found that these amphiphiles form thinner nonpolar layers than do conventional detergents in their crystalline lattice [37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At this time, it is not clear whether or not ganglio-TPAs form small PDCs relative to those formed with DDM. However, our previous study may shed light on the topic [37]. We recently reported the crystal structures of several N -oxide TPAs and found that these amphiphiles form thinner nonpolar layers than do conventional detergents in their crystalline lattice [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous study may shed light on the topic [37]. We recently reported the crystal structures of several N -oxide TPAs and found that these amphiphiles form thinner nonpolar layers than do conventional detergents in their crystalline lattice [37]. The means by which these TPAs arrange themselves therein show how the hydrophobic surface displayed by one TPA layer can accommodate that of an adjacent TPA layer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To test for detergents compatible with GOAT octanoylation, we screened initially at 1.5 × critical micelle concentration and at 1 mM for the following detergents: Anzergent 3–14, APO 10, Big Chap, Brij35, C13E8, CHAPS, CHAPSO, Cholate, CycloFos 6, CycloFos 7, Cymal 6, Cymal 7, Cy-TripGlu[28], Deoxy Big Chap, Deoxycholate, Digitonin, Dodecyl Maltoside, Fos-Choline-12, Fos-Choline-13, Fos-Choline-16, GDN [29], GNG-3 (Glucose Neopentyl Glycol)[30], Hexadecyl Maltoside, LysoFos-Choline 14, LysoFos-Choline 18, MNG-3 (Maltose Neopentyl Glycol)[31], Octyl Glucoside, Ph-TripGlu[28], Sucrose Monododecanoate, Taurocholate, TDAO (Tetradecyl Dimethylamine Oxide), Tetradecyl Dimethyl Glycine, Tetradecyl Maltoside, TRIPAO[32], and Triton X-100. Mixed micelles of cholesteryl hemisuccinate (CHS) plus CHAPS, MNG-3 (Lauryl Maltose Neopentyl Glycol), or Fos-Choline-16 were made by mixing detergent:CHS at ratios of 5:1, 10:1, and 20:1 (w/w), respectively, and added analogously at varying concentrations.…”
Section: Methodsmentioning
confidence: 99%